The effects of long-term testosterone treatment on endocrine parameters in hypogonadal men: 12-year data from a prospective controlled registry study - Aksam Yassin (14779204) (2022)
Testosterone therapy (TTh) is the primary treatment for aging men with functional hypogonadism. Whilst the benefits of testosterone (T) replacement are well-evidenced, the long-term data for TTh on metabolic and endocrine parameters is limited. Here we present the effect of TTh on endocrine parameters in hypogonadal men at a 12-year follow-up. In this single-centre, cumulative, prospective, registry study, 321 hypogonadal men (mean age: 58.9 years) received testosterone undecanoate injections in 12-week intervals for up to 12 years. Blood samples were taken at every other visit to measure levels of total T (TT), calculated free T, sex hormone-binding globulin (SHBG), estradiol, luteinizing hormone (LH), follicle-stimulating hormone (FSH), progesterone and prolactin. We observed an increase in TT of 15.5 nmol/L (p < 0.0001), a reduction in SHBG of 10.5 nmol/L (p < 0.0001) and an increase in calculated free T of 383.04 pmol/L (p < 0.0001) over the study period. This was accompanied by an increase in estradiol levels by 14.9 pmol/L (p < 0.0001), and decreases in progesterone (0.2 ng/mL, p < 0.0001), LH (10.4 U/L, p < 0.0001) and FSH (8.4 U/L, p < 0.0001) were demonstrated at 12-years. The levels of prolactin remained unchanged. Long-term TTh altered hormonal parameters to predictably modify the endocrine system. These effects were sustained during the entire observation time of 12 years. Other Information Published in: The Aging Male License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13685538.2022.2099828